2019
DOI: 10.1186/s12909-019-1897-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychiatric or social backgrounds on clinical decision making: a randomized, controlled multi-centre study

Abstract: BackgroundFrequent and repeated visits from patients with mental illness or free medical care recipients may elicit physicians’ negative emotions and influence their clinical decision making. This study investigated the impact of the psychiatric or social background of such patients on physicians’ decision making about whether to offer recommendations for further examinations and whether they expressed an appropriate disposition toward the patient.MethodsA randomized, controlled multi-centre study of residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Reflecting the international nature of the issue, included empirical studies originate from multiple countries and territories. Research comes from Australia (Ewart et al, 2016; Happell et al, 2016), Canada (Lowry et al, 2021), Japan (Yamauchi et al, 2019), the Netherlands (Bennebroek Evertsz' et al, 2020), Norway (Holm et al, 2014), Puerto Rico (Rivera‐Segarra et al, 2019), Spain (Martínez‐Martínez et al, 2021), Sweden (Fernholm et al, 2020), the United Kingdom (Chuttoo & Chuttoo, 2019; Nash, 2014; Noblett et al, 2017; Shefer et al, 2014, 2015; van Nieuwenhuizen et al, 2013) and the United States (Cabassa et al, 2014; Emmanuel et al, 2021; Geiss et al, 2018; Portier et al, 2017; Reeves et al, 2010a, 2010b). As is noted in a discussion of review limitations, the sample's geographic distribution is likely not representative of the scope of research on the issue due to exclusion of non‐English language publications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflecting the international nature of the issue, included empirical studies originate from multiple countries and territories. Research comes from Australia (Ewart et al, 2016; Happell et al, 2016), Canada (Lowry et al, 2021), Japan (Yamauchi et al, 2019), the Netherlands (Bennebroek Evertsz' et al, 2020), Norway (Holm et al, 2014), Puerto Rico (Rivera‐Segarra et al, 2019), Spain (Martínez‐Martínez et al, 2021), Sweden (Fernholm et al, 2020), the United Kingdom (Chuttoo & Chuttoo, 2019; Nash, 2014; Noblett et al, 2017; Shefer et al, 2014, 2015; van Nieuwenhuizen et al, 2013) and the United States (Cabassa et al, 2014; Emmanuel et al, 2021; Geiss et al, 2018; Portier et al, 2017; Reeves et al, 2010a, 2010b). As is noted in a discussion of review limitations, the sample's geographic distribution is likely not representative of the scope of research on the issue due to exclusion of non‐English language publications.…”
Section: Resultsmentioning
confidence: 99%
“…The stigmatization of individuals with mental illness occurs throughout societies, influencing the health professionals within them (Chuttoo & Chuttoo, 2019; Rivera‐Segarra et al, 2019). Further, stigma is identified as a key factor behind misdiagnosis of physical issues as psychosomatic in nature (Cabassa et al, 2014; Ho et al, 2022; Holm et al, 2014; Knaak et al, 2017; Lawson, 2018; Nash, 2014; Noblett et al, 2017; Reeves et al, 2010a, 2010b; Rivera‐Segarra et al, 2019; Shefer et al, 2014; van Nieuwenhuizen et al, 2013; Yamauchi et al, 2019). Individuals with mental illness may avoid seeking needed care due to fear of stigma from care providers (Bennebroek Evertsz' et al, 2020; Ewart et al, 2016; Happell et al, 2016; Holm et al, 2014; Martínez‐Martínez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research also found that medical students tend to physically touch patients with a low socioeconomic status more frequently. A recent study by Yamauchi et al (2019) investigating in the psychiatric and social background of patients found significant differences in clinical decision-making by physicians when patients had a medical history of schizophrenia.…”
Section: Empirical Data On the Prevalence Of Decision-making Biases In Medicinementioning
confidence: 99%
“…Furthermore, the number of visits to medical facilities tends to in-crease in patients involved with DPEs (7), which can affect the cost of medical care (7). Furthermore, DPEs are associated with diagnostic errors (8)(9)(10). Thus, DPEs have a significant detrimental impact on not only physicians but also the patients themselves and healthcare economics (3).…”
Section: Introductionmentioning
confidence: 99%